Protein oxidation and removal of oxidized proteins by proteolysis - Grune, Tilman (Henry Stewart Talks, 2007)
Oxidized proteins, Intracellular proteases, The 20S core proteasome, Proteasomal particles, The proteasome-ubiquitin system, Protein oxidation and proteasome, Degradation of oxidized proteins and protein function, Protein surface hydrophobicity, Unfolding of oxidized proteins, Stability of the 20S proteasome towards oxidation, Oxidative stress and protein turnover, Oxidation-induced proteolysis, Degradation of oxidized proteins in cells, What happens if degradation fails?, Protein aggregates inhibit the proteasome, Particle uptake by fibroblasts
Archived at 2018/05/31